KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS NON- PHARMACOLOGICAL MANAGEMENT OF HYPERTENSION AMONG PATIENTS AGED 40 – 75 YEARS IN WAKISO HEALTH CENTRE IV, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - DERRICK BONYO; Harrison Sida (Student's Journal of Health Research Africa, 2023)
Introduction: The specific objectives of the study were to assess knowledge, attitude, and practices towards non-pharmacological management of hypertension among patients aged 40-75 years in Wakiso Health Centre IV, District. Methodology: The study adopted a cross-sectional study design with a simple random technique as a sampling technique on a sample of 50 respondents. Data was collected using questionnaires with semi-structured and open-ended questions written in the English language; data was later analyzed manually and systematically by compiling percentages using Microsoft Excel computer program to generate bar graphs, tables, and pie charts. Findings: The knowledge of non-pharmacological management of hypertension showed that; almost all respondents (90%) had ever heard about non-pharmacological management of hypertension, (67%) obtained information health facility. The attitude towards non-pharmacological management of hypertension showed that; (78%) of respondents perceived hypertension to be extremely dangerous to their health, (70%) agreed that non-pharmacological management of hypertension is highly beneficial to their health, (56%) agreed that they could manage hypertension alone with non-pharmacological lifestyle modifications. from practices towards non-pharmacological management of hypertension depicted that; (56%) of respondents reported that they don’t smoke, (44%) daily they carry out physical exercises for 30 minutes, (40%) reported that they rarely add salt to their foods on the table and (52%) commonly feed on carbohydrates. Conclusion: The knowledge and attitude towards non-pharmacological management of hypertension were significant impressing though practices prerequisites some improvements to bridge the research gap since a notable number of participants were not entirely adopting self-care non-pharmacological practices Recommendation: Health Centre IV administration should sensitively continue to sensitize hypertensive patients on the importance of adopting fully non-pharmacological management practices to control hypertension, with a focus on identifying gaps in the research gap.